Assessment of Compassion Fatigue among Critical Care Nurses - Thoalfokar Mohammed Abdul Hussein; Dr. Jihad Jawad Kadhim (Zien Journals, 2022)
Critical-care units is one of the most demanding and challenging clinical arenas in healthcare settings. Nurses who work in those areas need careful attention and support due to its nature of stressful and complex workload. In order to provide optimum healthcare services and achieve best quality of patients’ nursing care, critical-care nurses’ feelings and emotions require continuous assessment to overcome those aspects.
Keywords: demanding; challenging; arenas